Geologia e quimioestratigrafia do Grupo Vazante em Lagamar (Minas Gerais, Brasil) - Carla Sofia de Sousa Marques (2015)
This work is based on a geological mapping at 1: 50.000 scale of an area of 400km2 around of Lagamar city (MG) and in isotopic profiles with stable isotopes of 13C, 18O and 87Sr/86Sr in Lagamar and Rocinha formations of the Vazante Group. In the region there are outcrop of rocksfrom the basal portion of Vazante Group in tectonic contact with the Bambui Group. There have been identified Santo Antonio do Bonito, Rocinha, Lagamar and Serra do Garrote Formations in Vazante Group, and in Bambui Group, Serra da Saudade and Lagoa Formosa Formations. The lithofacies study discriminated 10 facies associations identified in this work as marine sedimentary environments, ranging from shallow to deep. Two important reverse faults are included within themapped polygon, designated here as Lagamar fault I and II. Lagamar fault I put the older Serra do Garrote and Lagamar Formations upon Rocinha and Santo Antonio do Bonito Formations. Lagamar fault II put the Rocinha and Santo Antonio do Bonito formations (Vazante Group) on top of the Bambui Group. In Lagamar Formation, in Lavra Geraldo Americo, 13C show values between -0,14 and 0,91 and 18O between -6,89 and -3,18. In Antiga Lavra CALA, 13C are constant, between -0,86 and 2,2, and values of 18O are -9,82 to -3,54. In Rocinha Formation, CD05 show 13C values between -6,58 and -2,85 and, 18O values between -6,20 and -5,14. In F230A, 13C values are -6,62 to 3,33, and 18O values -10,25 to -7,54. This profiles may indicate diagenetic alteration, especially in Antiga Lavra CALA, because 13C and 18O show some co-variance in it chemostratigraphic profile. The values of 87Sr/86Sr of Lagamar Formation (0,70679; 0,70685; 0,70718 e 0,70788) may indicate Mesoproterozoic to Neoproterozoic Ages (Tonian/Cryogenian) for Lagamar Formation, and for Rocinha Formation (0,70766) Neoproterozoic Age (Cryogenian/Ediacaran).